Analisis Religios Value terhadap Green Purchase Attitude dan Green Purchase Intention : Studi Empiris pada Generasi Milenial Muslim - Nihayatu Aslamatis Solekah (Forum Inovasi Bisnis dan Manajemen, 2022)
The purpose of this study is to determine the effect of religious values ??on green purchase attitudes and green purchase intentions in empirical studies of the Muslim millennial generation. This study uses purposive sampling method with Muslim criteria and born between 1980-1999 with a sample of 369 respondents. The analysis test uses structural equation modeling Smart PLS. The results of this study indicate that the higher the religious value of the Muslim millennial generation, the more positive attitude they have towards environmentally friendly products (GPA). The higher the religious value of the millennial generation, they will have a stronger intention to buy green products (GPI). Likewise, Muslim millennials who have a positive attitude towards green products (GPA) will have a stronger intention to buy green products (GPI). This result is different from some previous research which stated that there is a gap between attitude and Green Purchase Intention. However, it turns out that Muslim millennials have a different behavior with their record getting more information about environmental sustainability.